Analysis of Stepped Impedance Microstrip Line Filter for S Band Application - Singh, Pravesh; Singh, Saurabh Kumar; Kumar, Amit; Gautam, Ruchita (IJRDO-Journal of Applied Science, 2018)
In this paper different order lowpass filter has been analyzed using Stepped Impedance method. For N=3 and N=6 the response has been compared. Microstrip line is one of the most popular type of planar transmission lines and is easily miniaturized and integrated with both passive and active microwave devices This paper fulfills the demand of newer microwave and millimeter-wave systems to meet the various issues such as cost, performance and size in the field of telecommunication. This paper presents a low insertion loss and the low-cost design S-lowpass filter(LPF) with the use of microstrip layout having the center frequency at 2.5GHz with the permittivity of value 4.4 and the height/thickness of the substrate is 1.5mm. The use of microstrip provides the advantages of simplicity and ease of fabrication. The design and simulation are performed by using the 3D full wave electromagnetic simulator IE3D.